1990
DOI: 10.1109/32.57627
|View full text |Cite
|
Sign up to set email alerts
|

A graph model for software evolution

Abstract: LUQIAbsfrucf-This paper presents a graph model of software evolution. We seek to formalize the objects and activities involved in software evolution in sufficient detail to enable automatic assistance for maintaining the consistency and integrity of an evolving software system. This includes automated support for propagating the consequences of a change to a software system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 11 publications
0
36
0
Order By: Relevance
“…Studies have shown that early parts of the system development cycle such as requirements and design specifications are especially prone to error (Luqi, 1989). Problems originating in the early stages often have a lasting influence on the reliability, safety and cost of the system.…”
Section: The Software Process Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have shown that early parts of the system development cycle such as requirements and design specifications are especially prone to error (Luqi, 1989). Problems originating in the early stages often have a lasting influence on the reliability, safety and cost of the system.…”
Section: The Software Process Problemmentioning
confidence: 99%
“…Software development processes such the hypergraph model for software evolution (Luqi, 1989), or the spiral model , improved the state of the art. However, all of them have a common weakness: risk assessment.…”
Section: The Risk Assessment and Estimation Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has module composition and powerful facilities to retrieve software components [17] and to support evolution [18].…”
Section: Small Large and Huge Grain Methodsmentioning
confidence: 99%